2013
DOI: 10.7860/jcdr/2012/4904.2681
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Clinical Evaluation of Once Daily Versus Alternate Day Application of Topical Clobetasol Propionate Cream in Psoriasis

Abstract: Background: Corticosteroids are extremely useful in the treatment of inflammatory skin disorders. Topical steroid applications are the most effective treatment for all types of psoriasis. Aims:To compare the efficacy of once daily versus alternate day application of topical steroid clobetasol propionate 0.05% (Tenovate cream®) in patients who have mild to moderate plaque psoriasis. Settings and Design:This study was conducted on 89 patients of plaque psoriasis, who attended the skin OPD in our hospital. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Topical preparations such as corticosteroids, anthralin, coal tar and retinoids, keratolytics, phototherapy, and systemic and biological medications such as immunosuppressants and monoclonal antibodies or their combinations are used to manage psoriasis. 1 Among the available topical steroids, CP has been found to be the most potent with proven efficacy in psoriasis apart from other steroid-responsive dermatoses. It prolongs the remission rates, thus enabling intermittent treatment schedules with minimum side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical preparations such as corticosteroids, anthralin, coal tar and retinoids, keratolytics, phototherapy, and systemic and biological medications such as immunosuppressants and monoclonal antibodies or their combinations are used to manage psoriasis. 1 Among the available topical steroids, CP has been found to be the most potent with proven efficacy in psoriasis apart from other steroid-responsive dermatoses. It prolongs the remission rates, thus enabling intermittent treatment schedules with minimum side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the anti-inflammatory, immunosuppressive, and antiproliferative effects of corticosteroids on the keratinocytes, they find a potent application in the management of several skin disorders. 1 Various factors, including body site, concentration of the drug, disease state, application method, and vehicle appropriateness, are generally considered when selecting a topical corticosteroid for the treatment of psoriasis or atopic dermatitis. 2 Clobetasol propionate (CP) 0.025% is a class I topical corticosteroid that is approved by the United States Food and Drug Administration for twice-daily application for the treatment of moderate-to-severe plaque psoriasis in patients aged 18 years or older.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid ointments are preferred to creams because they are less irritating to the sensitive vulvar tissue, and they do not contain alcohol or other preservatives [2]. The gold standard for the ultra‐potent class of corticosteroid treatment is clobetasol propionate 0.05% ointment, prescribed topically once daily for up to 4 weeks, then every other day for 4 weeks, then twice weekly for maintenance [8,9,22–24]. Prescribing intervals can be varied based on symptoms.…”
Section: Lichen Sclerosus (Ls)mentioning
confidence: 99%
“…The potential benefit of the use of high but not ultra‐potent TCS is minimization of side effects, including contact dermatitis, worsening of cutaneous skin infections, systemic effects, and skin atrophy. Clinicians should consider mometasone or triamcinolone as options for women who cannot tolerate clobetasol, for whom it is not effective or those at risk for side effects [11,23–27].…”
Section: Lichen Sclerosus (Ls)mentioning
confidence: 99%
“…Various studies have demonstrated the therapeutic benefits of alternating between different topical agents on different days, such as adding a weekday nonsteroidal agent to a weekend pulse therapy regimen [ 13 17 ]. A common sequential regimen with topical therapy consists of applying halobetasol propionate (HP), a potent topical corticosteroid, once daily in the morning, and using calcipotriol ointment, a vitamin D analogue, once daily in the evening for approximately 1 month [ 18 ].…”
Section: Introductionmentioning
confidence: 99%